Pre-harvest and post-harvest application of benzothiadiazole for controlling anthracnose and extending shelf life of harvested banana - Xueping, Li; Jingying, Shi; Xiaoyang, Zhu; Jinghua, Wang; Zhenxin, Yuan; Jun, Luo; Tongxin, Liu; Rong, Wang; Shen, Rao; Weixin, Chen (International Journal of Agricultural and Biological Engineering, 2013)
Abstract: Anthracnose, caused by the fungus Colletotrichum musae, is a serious latent post-harvest disease of banana, which results in major economic losses during transportation and storage. Benzo-thiadiazole-7-carbothioic acid S-methyl ester (BTH), a functional analogue of the plant endogenous hormone-like compound salicylic acid (SA), has been known to possess resistant effects on some diseases caused by fungi. The aim of present study was to select an appropriate BTH concentration and an appropriate stage of banana ripening for its application in controlling anthracnose and extending shelf life of harvested banana fruit. Different concentrations of BTH (50, 100, 200 and 300 μg/mL) were applied at different stages of banana fruit ripening, including one week, two weeks and one month before harvest. The results suggest that while the concentrations of BTH ranging from 50 μg/mL to 200 μg/mL in both pre-harvest and post-harvest application, this could control anthracnose of harvested banana fruit, the appropriate concentration of BTH in both pre-harvest and post-harvest treatment was 100 μg/mL and the best time of BTH treatment was two weeks before harvest. Examination of quality parameters including peel color and firmness indicated that 100 μg/mL BTH treatment delayed banana fruit ripening at room temperature.Keywords: banana fruit, shelf life, ripening, post-harvest preservation, BTH treatment, anthracnose, peel color, firmnessDOI: 10.3965/j.ijabe.20130604.009Citation: Li X P, Shi J Y, Zhu X Y, Wang J H, Yuan Z X, Luo J, et al. Pre-harvest and post-harvest application of benzothiadiazole for controlling anthracnose and extending shelf life of harvested banana. Int J Agric & Biol Eng, 2013; 6(4): 76－83.